Determinants of Blood Pressure Stability in Hypertensive Patients on Quality of Life - Dedi Maidiarto; Saimi Saimi; Sismulyanto Sismulyanto (Postgraduate, University of Mataram, 2026)
Hypertension is a global health problem with an increasing prevalence that impacts the quality of life of patients. This study aims to analyze the determinants of blood pressure stability and quality of life in hypertensive patients through a comprehensive multivariate approach. A cross-sectional design with a quantitative analytical approach was applied to 251 hypertensive patients undergoing routine treatment at primary health care facilities. Data collection used a validated standardized questionnaire to measure medication adherence, diet, physical activity, psychological stress levels, family social support, blood pressure stability, and quality of life. Data analysis included Chi-Square tests, Spearman's correlation, multiple linear regression, and multinomial logistic regression. The results showed that all independent variables had a significant relationship with blood pressure stability and quality of life. Diet showed the strongest correlation with blood pressure stability, while physical activity was the dominant predictor of blood pressure stability and quality of life. The regression model produced a coefficient of determination of 87.9% for blood pressure stability and 83.3% for quality of life, with classification accuracy reaching 95.2% and 96.4%, respectively. The findings indicate the importance of holistic interventions that integrate lifestyle modification, stress management, and strengthening social support in optimizing hypertension management to improve blood pressure stability and quality of life in patients